Optimizing the Diagnosis and Prevention of Tuberculosis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The peak of tuberculosis infection activity in the world occurred at the end of the 20th century. Tuberculosis is recognized by WHO as a global problem causing enormous economic and biological damage. If 20' years ago there was a decrease in morbidity and mortality from tuberculosis in the world, now 1/3 j' of the population is infected with Mycobacterium tuberculosisThe epidemiological situation of tuberculosis in different regions of the world is constantly changing as a result of the complex relationship between population movements, the number and distribution of tuberculosis patients , the socio-economic and cultural level of the population, the availability of medical care, and the prevalence of HIV infection.